2018
DOI: 10.1017/brimp.2018.9
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Adolescents for Life after School (PALS) Project: A Randomised Controlled Trial of a Coaching Intervention for Young People with Acquired Brain Injury

Abstract: Introduction: Existing resources to support adolescents with acquired brain injury (ABI) in transition from school to the ‘adult world’ are variable. This study evaluated an intervention using a coaching approach to support adolescents during this transition phase.Method: The study design was a parallel-group randomised controlled trial (RCT). Participants (n = 43) aged 14–19 years were randomised to intervention (n = 21) or no-intervention control (n = 21) conditions. The intervention group received six coach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Finally, the studies have collected samples of participants with different disabilities to study their support needs. Specifically, the support needs of adults with psychiatric disorders [ 39 , 46 , 47 , 60 , 75 , 90 ], motor disability [ 40 , 61 , 72 , 87 , 89 , 91 , 92 , 93 ] or several of these [ 42 , 109 ]; and youth with autism spectrum disorders [ 83 , 84 ] and motor disability, primarily cerebral palsy [ 31 , 32 , 50 , 88 ] have been studied.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the studies have collected samples of participants with different disabilities to study their support needs. Specifically, the support needs of adults with psychiatric disorders [ 39 , 46 , 47 , 60 , 75 , 90 ], motor disability [ 40 , 61 , 72 , 87 , 89 , 91 , 92 , 93 ] or several of these [ 42 , 109 ]; and youth with autism spectrum disorders [ 83 , 84 ] and motor disability, primarily cerebral palsy [ 31 , 32 , 50 , 88 ] have been studied.…”
Section: Resultsmentioning
confidence: 99%
“…The support needs scores have been used to assess the effectiveness of six interventions [ 51 , 62 , 68 , 73 , 74 , 92 , 108 ], focused on the development of life skills or related to employment. Of these, only Tate et al (2019) found no effect on support needs, as assessed through CANS, after applying a coaching program for transition to adulthood to youths with brain injury [ 92 ].…”
Section: Resultsmentioning
confidence: 99%